Young People's Experience of Foster Placement Breakdown: A Briefing Note - Tobin, Sinead (My University, 2015)
This research study was undertaken by Sinead Tobin, BSS, NQSW, MScASR, as part of the degree of Masters in Applied Social Research, Trinity College Dublin. The specific topic of placement breakdown was chosen, as, from the outset, the researcher, through her experience as a social worker with the Child and Family Agency, had a keen interest in the issue of placement disruption. This interest was founded from that fact that, both from an anecdotal and experiential point of view, disruption appeared to be a significant and escalating challenge within the care system. Presently, there is a substantial body of literature, albeit predominantly international, on the phenomenon of foster care placement breakdown, which reveals the pervasiveness of breakdown, with some studies citing prevalence rates ranging between 20% (Minty, 1999) and 47% (Wilson et al, 2000). The existing body of literature also highlights the harmful effects of disruption, or what Brown and Bednar (2006) refer to as the ‘cost’ of placement breakdown, to all parties involved including the young people, foster carers and indeed social workers. In light of the prevalence and known negative outcomes connected to placement breakdown, much of the literature on disruption has focused on examining risk and protective factors associated with breakdown, and therefore these studies have, overwhelmingly adopted quantitative approaches (Unrau, 2007). A clear and considerable gap in the literature on disruption is that very few studies have gone beyond examining the predictors, or what Barber and Delfabbro (2004) refer to as the ‘sterile indicators’, of placement breakdown and little is known about the lived experience of placement disruption for those mostly closely involved in it, particularly the young people themselves (Rostill-Brookes et al, 2011). To redress this gap, the researcher chose to interview young people who had been in care and who had experienced foster care placement breakdown.
PUBLISHED
Keywords: Inclusive Society; FOSTER CARE; Social Work; children's voice